Optical coherence tomography in neurological diseases - Calabresi, Peter A.; Balcer, Laura J.; Frohman, Elliot M. (Cambridge : Cambridge University Press, 2015)
Optical coherence tomography (OCT) provides tissue morphology imagery at much higher resolution than other imaging modalities such as MRI or ultrasound, and the machines are comparatively cheaper. It is an easy technique to perform; is non-ionizing, and therefore safe. These benefits are driving a rapid transformation of OCT, from its principal application as a research tool, into an extension of the 'neurological examination' in routine office practice. Originally used in assessing the severity of tissue damage and prognosis of multiple sclerosis and various neuro-ophthalmic conditions, OCT is increasingly used in other neurological disorders such as Parkinson's disease, ALS, and Alzheimer's disease. This book is the first comprehensive review of the use of OCT in neurological diseases. The coverage includes a description of the technique and its utilization in a variety of neurologic conditions. Essential reading for neurologists, neuro-ophthalmologists, and neuroradiologists wanting an introductory account of the clinical applications of OCT.
Machine generated contents note: Preface; 1. Introduction to optical coherence tomography in neurological diseases Peter A. Calabresi, Laura J. Balcer and Elliot M. Frohman; 2. Basic principles of optical coherence tomography Sven Schippling; 3. Anatomy of the anterior visual pathway Devin D. Mackay, Stephen L. Galetta and Sashank Prasad; 4. Optical coherence tomography in acute optic neuritis Andrew P.D. Henderson, S. Anand Trip and David H. Miller; 5. Optical coherence tomography and visual outcomes in acute optic neuritis Fiona Costello; 6. Optical coherence tomography and low contrast acuity Shin C. Beh and Laura J. Balcer; 7. Optical coherence tomography and electrophysiology of the visual pathway A. Klistorner, C.L. Fraser, C. Yiannikas and S.L. Graham; 8. Optical coherence tomography and electrophysiology of the optic nerve head Shin C. Beh, Zane Schnurman, Darrel Conger, Amy Conger, Benjamin M. Greenberg, Elliot M. Frohman and Teresa C. Frohman; 9. Meta-analysis of optical coherence tomography in multiple sclerosis Axel Petzold; 10. Optical coherence tomography and brain MRI in multiple sclerosis Shiv Saidha and Peter A. Calabresi; 11. Optical coherence tomography in neurodegenerative diseases Friedemann Paul and Alexander Ulrich Brandt; 12. Optical coherence tomography pathologies to know about in clinical practice Scott Newsome and John N. Ratchford; 13. Optical coherence tomography and retinal segmentation in neurological diseases Elias S. Sotirchos and Shiv Saidha; 14. Optical coherence tomography and retinal pathology in neurologic diseases Ari J. Green; 15. Retinal inflammation in MS revealed by optical coherence tomography and ophthalmoscopy Elena H. Martinez-Lapiscina, Bernardo Sanchez-Dalmau and Pablo Villoslada; 16. Optical coherence tomography and optic nerve MRI in demyelinating diseases Robert T. Naismith; 17. Optical coherence tomography in neurologic clinical trials Robert A. Bermel and Peter K. Kaiser; 18. Optical coherence tomography in multi-center setting: quality control issues Axel Petzold, Laura J. Balcer, Peter A. Calabresi, Fiona Costello, Elliot M. Frohman, Ari J. Green, Sasha Klistorner, Friedemann Paul, Sven Schippling and Pablo Villoslada; 19. Future technological advances in optical coherence tomography Hiroshi Ishikawa and Joel Schuman; Index.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Nervous system -- Diseases -- Diagnosis; Central nervous system -- Tomography